2001
DOI: 10.1191/026921501678310199
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the effects of weighted garments on balance and gait of stroke patients with residual disability

Abstract: We found no evidence to support the clinical use of these weighted garments for stroke survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…The STEP was found in the present study to have a substantive effect on the gait velocity of stroke survivors. This finding contrasts with the study of Pomeroy et al [12], who reported no significant difference in the gait velocity between the treatment and the control groups among stroke survivors following the STEP. In a related study carried out by States et al [15], on overground physical therapy gait training for chronic stroke patients with mobility deficits, an insignificant finding was also reported.…”
Section: Discussioncontrasting
confidence: 99%
“…The STEP was found in the present study to have a substantive effect on the gait velocity of stroke survivors. This finding contrasts with the study of Pomeroy et al [12], who reported no significant difference in the gait velocity between the treatment and the control groups among stroke survivors following the STEP. In a related study carried out by States et al [15], on overground physical therapy gait training for chronic stroke patients with mobility deficits, an insignificant finding was also reported.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the meta-analyses for interventions related to gait and mobility-related functions and activities are summarized in figure 2 (for details see table S2A in file S1). Pooling was not possible for bilateral leg training with rhythmic gait cueing [30], mirror therapy for the paretic leg [31], mental practice with motor imagery [32], limb overloading with external weights [33], systematic verbal feedback on gait speed [34], maintenance of ankle dorsiflexion by using a standing frame or night splint [35], manual passive mobilization of the ankle [36], range of motion exercises of the ankle with specially designed equipment [37], ultrasound for the paretic leg [38], segmental muscle vibration for a drop foot [39], whole body vibration [40], and wheel chair propulsion [41].…”
Section: Resultsmentioning
confidence: 99%
“…The use of an anterior ankle-foot orthosis (AFO), giving support to the ankle joint and the ventral side of the tibia, has been shown to increase the maximum weight loaded on the paretic leg from 54% to 61% in 24 patients in the chronic phase of stroke, without affecting postural stability [54]. Weighted garments probably have no effect on functional balance or gait in patients with stroke [55]. In conclusion, aids such as shoe adaptations or AFOs may be able to improve substantially spontaneous weight bearing, whereas canes may be able to improve both weight distribution and stance stability in individuals with stroke.…”
Section: Effects Of Aidsmentioning
confidence: 99%